The effect of yin yoga intervention on state and trait anxiety during the COVID-19 pandemic - Somere, Kristīne; Munkevics, Maris; Krams, Ronalds; Rača, Gunta; Luoto, Severi; Krams, Indrikis (Frontiers in Psychiatry, 2024)
Introduction: Although some findings indicate that yoga can reduce stress and anxiety, many studies present mixed results. The potential of yoga interventions to alleviate anxiety, including the mechanisms and boundary conditions by which it does so, is an under-researched topic. Anxiety is often divided into "state anxiety" and "trait anxiety," the former being a temporary reaction to stressful events, while the latter is a more stable personality feature that responds to adverse situations or perceived threats. Materials and methods: This study investigates whether a yin yoga intervention delivered online reduces state anxiety immediately after each yoga session and whether the anxiety levels are significantly lower at the end of the 10-week yoga intervention than at the beginning of the study. We also predicted no effect of yin yoga intervention on trait anxiety. The study was conducted during the COVID-19 pandemic when participants (N = 48 Latvian women) experienced heightened anxiety levels. Results: This study shows that a ten-week online yin yoga intervention significantly reduced state anxiety in the intervention group compared with the control group. State anxiety levels also significantly decreased after each yin yoga session, providing more support for the anxiety-reducing effect of yin yoga. In contrast, yoga participation did not cause differences in trait anxiety between the control and intervention groups, even though trait anxiety decreased in the intervention group and increased in the control group over the study period. Conclusion: The positive effects of yin yoga on state anxiety indicate the potential of yin yoga intervention as a first-line treatment to control and reduce state anxiety, with possible additional effects on trait anxiety.